Development of a Patient-reported Experience and Outcome Measures in Pediatric Patients Undergoing Bowel Management for Constipation and Fecal Incontinence. Issue 2 (August 2019) - Halleran, Devin R.; Lane, Victoria A.; Leonhart, Karen L.; Fischer, Beth; Sebastião, Yuri V.; Chisolm, Deena J.; Levitt, Marc A.; Wood, Richard J.; Minneci, Peter C.; Deans, Katherine J.
ABSTRACT: Aims and Objectives: The aim of this review is develop a reliable and valid questionnaire that assesses patient-reported experience measures (PREMs) and patient-reported outcome measures (PROMs) of caregivers, families, and patients with severe constipation and fecal incontinence who failed conservative treatments and require a formal bowel management program (BMP). Methods: A 5-step iterative process was utilized to ensure the reliability and validity of the final instrument. Parents or guardians of patients undergoing our week-long BMP were first asked 20 open-ended questions aimed at understanding the challenges in managing their child's condition. Responses were transformed into an initial 41-item survey constituted of 2 constructs relating to PREMs (24 items) and PROMs (17 items). Survey items were then administered to 359 parents and guardians undergoing BMP. Cognitive interviews were performed with 20 families to assess face validity and to further refine the survey. Instrument readability and reliability was assessed by Flesch-Kincaid and Crohnbach α analyses. Items that weakly correlated were deleted to yield a final instrument that was both valid and reliable. Results: A 33-statement survey was developed that encompasses important physical and emotional health concerns, quality of life, treatment success, financial considerations, schooling, parental employment, and social concerns. The final instrument, the Patient-Reported Experience and Outcome Measure in a Bowel Management Program (PREOM-BMP), is divided into 2 separate constructs that assess important patient-reported experience (22 items) and outcome (11 items) measures. Reliability analyses on the final instrument yielded a Crohnbach α of 0.925. Conclusions: The PREOM-BMP offers physicians and nursing professionals a brief and valid tool to measure the impact of a bowel management program on both the child and the family unit. Abstract : Supplemental Digital Content is available in the text